Normalization of blood clotting characteristics using prothrombin complex concentrate, fibrinogen and FXIII in an albumin based fluid: experimental studies in thromboelastometry - Koller, Tobias (Scand J Trauma Resusc Emerg Med, 2021)
BACKGROUND: Colloid fluids supplemented with adequate combinations of coagulation factor concentrates with the capability to restore coagulation could be a desirable future treatment component in massive transfusion. METHODS: Starting from a coagulation factor and blood cell-free albumin solution we added Prothrombin Complex Concentrate, Fibrinogen Concentrate and Factor XIII in different combinations and concentrations to analyze their properties to restore thromboelastometry parameters without the use of plasma. Further analysis under the presence of platelets was performed for comparability to whole blood conditions. RESULTS: Albumin solutions enriched with Fibrinogen Concentrate, Factor XIII and Prothrombin Complex Concentrate at optimized concentrations show restoring coagulation potential. Prothrombin Complex Concentrate showed sufficient thrombin formation for inducing fibrinogen polymerization. The combination of Prothrombin Complex Concentrate and Fibrinogen Concentrate led to the formation of a stable in vitro fibrin clot. Fibrinogen and Factor XIII showed excellent capacity to improve fibrin clot firmness expressed as Amplitude at 10 min and Maximal Clot Firmness. Fibrinogen alone, or in combination with Factor XIII, was able to restore normal Amplitude at 10 min and Maximal Clot Firmness values. In the presence of platelets, the thromboelastometry surrogate parameter for thrombin generation (Clotting Time) improves and normalizes when compared to whole blood. CONCLUSIONS: Combinations of coagulation factor concentrates suspended in albumin solutions can restore thromboelastometry parameters in the absence of plasma. This kind of artificial colloid fluids with coagulation-restoring characteristics might offer new treatment alternatives for massive transfusion. TRIAL REGISTRATION: Study registered at the institutional ethic committee “Institut de Recerca, Hospital Santa Creu i Sant Pau, with protocol number IIBSP-CFC-2013-165.